Esketamine as an Epidural Adjuvant for Postoperative Analgesia in Gynecological Malignancy Surgery: A Randomized Trial - Luo H; Yang Y; He Z; Pan C; Wu X; Cao S; Zhang J (Journal of Pain Research)
Huanyu Luo,1,2,* Yuecheng Yang,1,2,* Zhiyong He,1,2 Congxia Pan,1,2 Xing Wu,1,2 Shumei Cao,1,2 Jun Zhang1,2 1Department of Anesthesiology, Fudan University Shanghai Cancer Center, Shanghai, People’s Republic of China; 2Department of Oncology, Shanghai Medical College, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Zhang, Department of Anesthesiology, Shanghai Cancer Center, Fudan University, No. 270 Dong-An Road, Shanghai, 200032, People’s Republic of China, Tel +86-021-64175590, Fax +86-021-64174774, Email snapzhang@aliyun.comObjective: This study aims to evaluate the efficacy of esketamine as an epidural adjuvant in mitigating postoperative pain, particularly following the discontinuation of epidural analgesia in patients undergoing open surgery for gynecological malignancies.Design: A randomized controlled trial.Methods: Eighty-eight patients were randomized to receive either esketamine (0.4 mg/kg) combined with sufentanil and ropivacaine (eskatamine group) or sufentanil and ropivacaine alone (control group) via patient-controlled epidural analgesia. Primary outcomes included pain scores on postoperative day 3, assessed using the numeric rating scale. Secondary outcomes included pain scores on postoperative days 1 to 4, Quality of Recovery-15 scores, rescue analgesic requirements, and adverse events.Results: The eskatamine group demonstrated a significant reduction in nocturnal pain intensity on postoperative day 2 compared with controls (median 3.0 vs 4.0, P = 0.044), with fewer patients requiring rescue analgesics on postoperative day 3 (13.4% vs 32.6%, P = 0.036). However, no significant differences were observed in rest pain, movement pain, or breakthrough pain across postoperative day 1– 4. Subgroup analysis revealed higher Recovery-15 scores for moderate pain in the esketamine group (median 10 vs 9, P = 0.048). Transient dizziness was more frequent in the esketamine group (47.7% vs 23.3%, P = 0.017), but no persistent adverse effects were observed.Conclusion: Esketamine, as an adjuvant in patient-controlled epidural analgesia, reduced nocturnal pain on postoperative day 2, shorten the moderate pain duration and lower rescue analgesics within 24 hours after the removal of analgesia device. However, it did not affect pain scores although less rescue analgesia was needed on postoperative day 3.Keywords: esketamine, postoperative pain, epidural analgesia, recovery quality, gynecological malignancy